Default risk on Finnish government foreign currency debt - Erja Saukkonen (Bank of Finland, 1995)
This paper is a study of default risk on Finnish government debt. The objectives of the study are to estimate the size of the default risk and to shed some light to the causes of default risk, using simple regression runs.To estimate the Finnish government default risk premium, we measured the interest rate differential on Finnish government DEM- and USD-denominated bonds compared to respectively German and US government bonds over the period October 1991 February 1995.For the sake of comparison, we also measured the interest rate differential between Finnish government FIM-denominated bonds and German government bonds.Our results indicate that for the period studied the default risk premium on the Finnish government foreign-currency denominated debt was quite small, but by no means trivial and clearly not constant.The default risk premium on DEM-denominated debt was a small fraction of the differential for FIM-denominated debt.Our results provide strong evidence that the default risk premium was mainly determined by the level and growth rate of government debt and was not related to the general economic indicators (GDP and current account).
URN:NBN:fi:bof-20140807216
Keywords: 330